A Novel HWRR-SJF Scheduling Algorithm for Optimal Performance Improvement in LTE System - Pradeep S (International Journal of Engineering Education, 2019)
In currently, the revolution in a high-speed broadband network is the requirement and also endless demand for high data rate and mobility. To achieve above requirement, the 3rd Generation Partnership Project (3GPP) has been established the Long Time Evolution (LTE). LTE has established an improved LTE radio interface named LTE-Advanced (LTE-A) and it is a promising technology for providing broadband, mobile Internet access. But, better Quality of Service (QoS) to provide for customers is the main issue in LTE-A. To reduce the above issue, the packets should be utilized by using one of the most significant function of packet scheduling to upgrading system performance via determines the throughput performance. In existing scheme, the user with poor Channel Quality Indicator (CQI) has smaller throughput issue is not focused. In this paper, a Hybrid Weighted Round Robin with Shortest Job First (HWRR-SJF) Scheduling technique is proposed to enhance efficient throughput and fairness in LTE system for stationary and mobile users. In this proposed scheduling, to schedule users according to a different criterion like fairness and CQI. HWRR-SJF Scheduling has been proposed for scheduling of the users and it produces increased throughput for various SNR values simulated alongside Pedestrian and Vehicular moving models. The proposed method also uses a 4G-LTE filter or Digital Dividend (DD) in order to align the incoming signal. The digital dividend is used to remove white spaces, which refer to frequencies assigned to a broadcasting service but not used locally. The proposed model is very effective for users in terms of the performance metrics like packet loss, throughput, packet delay, spectral efficiency, fairness and it has been verified through MATLAB simulations.